Recurrent readings of Cuba and José Martí. Gravity against air - Serna Arnaiz, Mercedes (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
After a short introduction to the life of José Martí in Spain, this article analyses the need of some Cuban writers to dismantle on the one hand Marti’s hagiographic status promoted by the Castro regime and on the other the trope of Cuba as a paradise, in the style of Lezama Lima, "where life is so good" — the two main axes around which the work of the Cuban intellectuals "from inside" revolves.